2013
DOI: 10.1590/s1516-35982013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Performance, carcass characteristics and gain cost of feedlot cattle fed a high level of concentrate and different feed additives

Abstract: The objective of this study was to evaluate the effects of feeding cattle with isoprotein and isoenergetic diets, with and without the addition of polyclonal antibody preparation (PAP), yeasts (YST) or monensin sodium (MON) on performance, carcass characteristics and gain cost in feedlot. Ninety-five 20-month old bullocks (323.3±21.8 kg) were distributed in 25 pens. The completely randomized experimental design had a 2 × 2 + 1 factorial arrangement and the treatments were replicated 5 times. There was no effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
(27 reference statements)
1
5
1
2
Order By: Relevance
“…In present study, cattle fed low plane of nutrition diet supplemented with ADY 4 g/head/d significantly increased ADG, and achieved to a comparable level with cattle fed with high plane of nutrition diet, which was in agreement with the research of Geng et al [18]. Previous studies have shown that the supplementation with ADY could increase ruminant animals DMI [19], however there were also some studies showed that DMI could be reduced [20,21]. Our results indicated that dietary supplementation with ADY had no significant effect on DMI, which was consistent with the result reported by Vyas et al [22].…”
Section: Discussionsupporting
confidence: 92%
“…In present study, cattle fed low plane of nutrition diet supplemented with ADY 4 g/head/d significantly increased ADG, and achieved to a comparable level with cattle fed with high plane of nutrition diet, which was in agreement with the research of Geng et al [18]. Previous studies have shown that the supplementation with ADY could increase ruminant animals DMI [19], however there were also some studies showed that DMI could be reduced [20,21]. Our results indicated that dietary supplementation with ADY had no significant effect on DMI, which was consistent with the result reported by Vyas et al [22].…”
Section: Discussionsupporting
confidence: 92%
“…Haddad and Goussous (2005) reported a higher daily weight gain in lambs that received 3 g d −1 Saccharomyces cerevisiae, and this variable related with increases in the digestibility coefficients of the organic matter, nitrogen, and neutral detergent fiber. The better feed conversion in our study related to Saccharomyces cerevisiae supplementation could indicate a higher feed digestibility and greater efficiency of nutrient utilization (Rodrigues et al, 2013;Elghandour et al, 2014;Arowolo and He, 2018). However, our results did not show differences in digestibility coefficients of the diet.…”
Section: Discussioncontrasting
confidence: 44%
“…Feed intake responses of beef cattle to live yeast (LY) supplementation have been variable; some studies reported increased DMI (Robinson, 2010;Habeeb, 2017), whereas, other studies stated a reduction of DMI (Rodrigues et al, 2013;Sartori et al, 2017). Furthermore, there appears to be more studies that report no impact of LY supplementation on DMI than studies that report positive or negative effects (Beauchemin, 2012).…”
Section: Effect Of Yeast Supplementation On Growth Performance and Camentioning
confidence: 99%